Since you’re given the equation, y = 6x + 6, all you need to do is replace x with the given table of values to get the corresponding y-values.
x = -1:
y = 6x + 6
y = 6(-1) + 6
y = -6 + 6
y = 0 (This is the y-value for x = -1).
x = 0:
y = 6x + 6
y = 6(0) + 6
y = 0 + 6
y = 6 (This is the corresponding y-value of x = 0).
x = 1:
y = 6x + 6
y = 6(1) + 6
y = 6 + 6
y = 12 ( this is the corresponding y-value of x = 1).
I will leave the rest for you to solve, since you already have an idea how to work out the given problem by following the steps that I’ve taken. That way, you’ll learn and get used to doing these types of problems. If you have any questions, just let me know.
Please mark my answers as the Brainliest, if you find this helpful :)